Democracy promotion and presidential term limits - Nowack, Daniel (2023)
The end of the Cold War saw an unprecedented diffusion of democracy. This diffusion went hand in hand with the emergence of international democracy promotion. Through democracy promotion, democratic states attempt to support and protect democratic institutions around the world by means of bilateral and multilateral international cooperation as well as development cooperation. Yet, the 'wave of democratization' has ebbed away since the Cold War. Rather than an anabated spread of democracy, many countries that seemed on a transition-path to democracy are now stuck in a political state between autocracy and democracy, where democratic institutions formally exist but are compromised by authoritarian practices. Moreover, populist movements, illiberalism, and non-democratic institutional changes seem to challenge democracy as a political system even in countries where it was long since regarded as historically and socially consolidated. This as well as the increasing confidence of authoritarian regimes threaten to jeopardize the strides that worldwide democratization has made in the past three decades. Against this setting, the present thesis investigates the effectiveness of international democracy promotion in supporting and guarding the democratic institutionalization of political power. The research presented here zooms in on presidential term limits, a political institution meant to prevent the personalization of political power and ensure rotation in presidential office. While it was characteristic for countries, particularly in sub-Saharan Africa, that began transitioning to democracy at the end of the Cold War to introduce presidential term limits in their newly designed constitutions, many of these provisions have since been challenged by incumbent presidents. Research shows that the evasion of term limits is associated with a worsening of the general state of democracy in a country. Evasion of presidential term limits is thus seen as an important manifestation for the weak institutionalization and further de-institutionalization of democracy. Although presidential term limits and in particular their circumvention have hence become a subject matter of interest to political scientists, many scholars do not focus in this regard explicitly on the role of international democracy support. I address this gap by studying the influence that international democracy promotion has on the evasion and introduction of presidential term limits. The first chapter provides a conceptual and theoretical introduction to presidential term limits and their relation to the weak institutionalization of democracy. Democracy promotion and the different forms it may take is also introduced before a brief outlook on the thesis is presented. In chapter two my co-author and I present a broad perspective on how democracy aid, which is the implementation of democracy promotion as foreign aid in development cooperation, is associated with the risk that presidents attempt to evade term limits as well as that they actually succeed in doing so. In chapter three, my co-author and I undertake a qualitative paired comparison of two cases where incumbent presidents attempted to circumvent a term limit but failed at different stages during the process. We compare the role that different means, or 'instruments' of democracy promotion played in both cases and how their effectiveness was predicated on favourable domestic conditions, particularly popular pro-democratic attitudes. In chapter four, I provide an 'in-depth' description of one of the two cases. The chapter employs a qualitative methodology designed to trace closely the influence of different factors for an outcome. I make use of this by systematically assessing how different democracy promotion instruments acted alone and in conjunction with domestic factors on the case's outcome. Finally, chapter five shifts the focus from the evasion of term limits to the introduction of term limits. Interested in the 'on-the-ground' practice of democracy promotion during ad hoc emerging reform episodes, I study the interactions between on the one hand domestic civil society and political opposition parties and on the other hand external embassies and international organizations. The research results show that international democracy promotion often has a limited, conditional influence on preventing the de-institutionalization of democracy. While it is evident according to a presented statistical analysis that democracy promotion through foreign aid is associated with lower risks of term limit evasions, this relation is substantial in effect size only for medium to high per capita-amounts of democracy aid. Furthermore, results of the qualitative case studies show that democracy promotion operates through largely two mechanisms, a 'hard power' mechanism functioning according to a logic of consequentiality, conditionality, and leverage; and a 'soft power' mechanism functioning according to a logic of appropriateness and linkage. However, both work best in tandem, and are predicated on domestic conditions, particularly on favourable popular (pro-)democratic attitudes and a civil society that is free to mobilize. Finally, the research presented here also emphasizes the quandaries to which democracy promoters themselves are subject, especially when they need to respond ad hoc to a push for political liberalization in an hitherto (semi-)authoritarian country context. The thesis contributes to two interescting research fields, one on the evasion of presidential term limits, and the other on the role that international democracy support can play in preserving and promoting democratic institutions. Its results suggest policy implications particularly for the practice and implementation of democracy promotion. Foremost among these are that the level of spending of democracy aid in development cooperation as well as its temporal continuation can have substantial effects on guarding democratic institutions (chapter two); that 'hard power' and 'soft power' approaches of democracy promotion need to be used wisely in complementarity to one another (chapter three and four); that foreign states and international organizations need to react decisively against the curbing of the civic space, and also need to defend institutions integral to 'democracy as democracy' against transgressions and violations (chapters three to five); and finally, that democracy supporters, particularly foreign governments as democracy supporters, need to critically reflect on self-imposed internal restraints besides encountered external constraints in the practice of international democracy promotion.
Keywords: Hochschulschrift